2022
DOI: 10.1177/10732748221140691
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and Its Associations With Anxiety and Depression Among Newly Diagnosed Patients With Breast Cancer: A Retrospective Observational Cohort Study in a US Commercially Insured and Medicare Advantage Population

Abstract: Background Multimorbidity is common in patients with breast cancer, thus increasing the complexity of cancer care and economic burden, worsening their prognosis and quality of life. The prevalence of multimorbidity and its influence on psychological distress among patients with breast cancer have not been well characterized. Objectives To examine the prevalence of multimorbidity and its associations with anxiety and depression among newly diagnosed patients with breast cancer. Methods We conducted a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…Moreover, multiple comorbidities are common among patients with breast cancer and are associated with increased risk of anxiety and depression in the first year following breast cancer diagnosis. 19 Due to limited availability of specialized psychological care for patients with cancer, 17,18 there is a growing need for new treatment modalities, such as digital therapeutics. A recent review suggests that digital therapeutics in oncology possess clinical value, provide benefits perceived by both patients and healthcare providers, and may have a positive impact on HCRU, although further research is needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, multiple comorbidities are common among patients with breast cancer and are associated with increased risk of anxiety and depression in the first year following breast cancer diagnosis. 19 Due to limited availability of specialized psychological care for patients with cancer, 17,18 there is a growing need for new treatment modalities, such as digital therapeutics. A recent review suggests that digital therapeutics in oncology possess clinical value, provide benefits perceived by both patients and healthcare providers, and may have a positive impact on HCRU, although further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study design and data source have been published previously. 19 Detailed inclusion and exclusion criteria are described in Supplementary Figure S1. The database includes over 20 million Aetna members and contains patient-level data including inpatient and outpatient data, and medical and pharmacy claims of fully insured commercial health plan and Medicare Advantage members.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 42 most common chronic conditions in the Aetna claims data were included and identified using previously described methods based on ICD-10-CM codes. 8,15 The list of each chronic condition, its acronym or abbreviation, and the corresponding ICD-10-CM codes used in this study are reported in Supplementary Table S1. We included 18 of the 20 comorbid conditions recommended by the US Department of Health and Human Services for studying multimorbidity because they are chronic, prevalent, and potentially amenable to intervention.…”
Section: Assessment Of Comorbidity and Multimorbiditymentioning
confidence: 99%